Fluorinated interfacial layers in perovskite solar cells: efficient enhancement of the fill factor. Issue 32 (31st July 2020) - Wang, Ru; Nakar, Rana; Jiang, Yue; Berton, Nicolas; Wu, Sujuan; Wang, Qianming; Liu, Jun-Ming; Zhou, Guofu; Kempa, Krzysztof; Schmaltz, Bruno; Gao, Jinwei
Abstract : A series of novel fluorinated small molecules have been designed and used as interfacial materials to improve the contact between perovskite and spiro-OMeTAD, with an enhanced PCE enabling by a significant FF, up to ∼80%. Abstract : The fill factor is a key parameter in perovskite solar cells and is strongly influenced by interfacial charge transfer processes and subsequently impacts the power conversion efficiency. Herein, to improve the fill factor, three fluorine substituted materials were designed, synthesized and characterized. By inserting them as thin interfacial layers at the perovskite/spiro-OMeTAD interface, the electron blocking properties and the hole extraction and transfer efficiency were simultaneously enhanced, resulting in an enhancement of the fill factor from 75% up to ∼80% while keeping the short-circuit current and the open-circuit voltage unchanged. Furthermore, the introduction of fluorine atoms increases the hydrophobicity, leading to an enhanced device stability.